The Influence of Using I Spy Game towards Students’ Vocabulary Mastery - Shaumi Fitria; Iskandar Abdul Samad; Nira Erdiana (Research in English and Education Journal, 2021)
Vocabulary is one of the basic and most important aspects in learning a language. In the learning process, learners need to know lots of words of the target language with such various techniques. Students’ vocabulary mastery is influenced by many factors. In this research, researcher wants to know if there is significant influence towards the students’ vocabulary mastery by using a game called I Spy as the technique used in this research. This research is a quantitative approach with pre-experimental design, one group pretest-posttest. The subjects of this research were the first grade students of junior high school. The class chosen as the experimental class was VII2 which consisted of 30 students at SMP Negeri 2 Takengon with 15 female students and 15 male students. The data was collected from the pretest and posttest result and analyzed by using statistical formula. The analysis result of this study proved that the students’ posttest scores are significantly increased higher than the pretest scores which the mean of pretest was 46.7 and the mean of posttest was 70.5 and the gain between the means was 23.8. According to the data analysis result, it can be inferred that students’ tests scores increased after the I Spy game technique was applied which means that it also influences students’ vocabulary mastery.